MORPHOLOGICAL AND GENOMIC VARIABILITY AMONG SCLEROTIUM ROLFSII POPULATIONS - RASU, THILAGAVATHI; SEVUGAPPERUMAL, NAKKEERAN; THIRUVENGADAM , RAGUCHANDER; RAMASAMY, SAMIYAPPAN (The Bioscan, 2013)
Isolates of Sclerotium rolfsii collected from different host plants and geographic locations in Tamil Nadu, India were examined for their morphological and genomic variations. Out of 17 isolates tested for their cultural morphology, most of them were observed with compact colonies and few were fluffy colonies. Based on growth rate, they were categorized into three groups such as slow growing, fast growing and intermediate. Number of sclerotia and dry weight of 100 sclerotia also varied among isolates appreciably. Mostly dark to light brown sclerotia was observed for the isolates. RAPD banding patterns were established for 10 isolates of S. rolfsii using five random primers. Size of DNA fragments amplified by all five primers ranged from 100 bp to > 1 kb indicating polymorphism among S. rolfsii isolates. The result from UPGMA based dendrogram generated for the S. rolfsii isolates revealed that they were divided into two main clusters which were further divided into subclusters. Overall, all the isolates have about 54% similarity coefficient indicating that they were genetically varied by their unique banding patterns however, they shared more number of common bands and clustered together. Hence this study clearly indicated that morphological and genetic variability existed among S. rolfsii isolates.